2004
DOI: 10.1159/000082028
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Alexithymia and Panic Disorder: A Longitudinal Study to Answer an Open Question

Abstract: Background: In the present study, we evaluated whether patients with panic disorder (PD) in complete remission were more alexithymic than normal controls. Methods: Fifty-two PD patients (both during the acute phase of the disorder and after at least 2 months of complete remission) and 52 age- and sex-matched normal subjects completed the Toronto Alexithymia Scale-20 and the Hamilton Rating Scales for Anxiety (Ham-A) and for Depression. Results: A higher rate of alexithymia was found in PD patients than in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 32 publications
8
71
0
5
Order By: Relevance
“…In line with findings in non-ASD samples (Bankier et al 2001;Berthoz et al 1999;Marchesi et al 2005), our study found that young people with ASD and co-occurring alexithymia reported significantly higher trait anxiety than those with ASD but without alexithymia. The high prevalence of anxiety in individuals with ASD is consistently reported (Simonoff et al 2008;White et al 2009), but the shared cognitive correlates between the two disorders remain under exploration (e.g.…”
Section: The Association Of Co-occurring Alexithymia With Emotional Dsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with findings in non-ASD samples (Bankier et al 2001;Berthoz et al 1999;Marchesi et al 2005), our study found that young people with ASD and co-occurring alexithymia reported significantly higher trait anxiety than those with ASD but without alexithymia. The high prevalence of anxiety in individuals with ASD is consistently reported (Simonoff et al 2008;White et al 2009), but the shared cognitive correlates between the two disorders remain under exploration (e.g.…”
Section: The Association Of Co-occurring Alexithymia With Emotional Dsupporting
confidence: 90%
“…Taylor et al (1999) propose that alexithymia is primarily a disorder of affect regulation, leading to difficulties in modulating the autonomic nervous system, thus resulting in hyper-arousal in response to stress. In line with this view, there are consistent reports of increased anxiety, particularly panic disorder, among non-ASD individuals with elevated alexithymia (Bankier et al 2001;Berthoz et al 1999;Marchesi et al 2005). Additionally, one prospective longitudinal study found that higher alexithymia in early adolescence was associated with the development of an anxiety disorder four years later (Karukivi et al 2014).…”
mentioning
confidence: 64%
“…With respect to the temporal stability of alexithymia, some longitudinal studies have suggested a trait view of alexithymia (e.g., Martinez-Sanchez, Ato-Garcia, & Ortiz-Soria, 2003), whereas the frequently observed association between alexithymia and depression or anxiety suggested a statedependent phenomenon (Honkalampi, Hintikka, Laukkanen, Lehtonen, & Viinamaki, 2001;Honkalampi et al, 2004;Marchesi, Fontò, Balista, Cimmino, & Maggini, 2005). Recent studies appear to have reached a consensus on this issue, however, by distinguishing absolute from relative stability.…”
Section: Is Alexithymia Stable or Can It Occur Secondary To Trauma Omentioning
confidence: 99%
“…The very concept of somatization, according to Wilhelm Steckel a psychoanalyst who introduced this term, means a tendency to being more aware of physical than men-Archives of Psychiatry and Psychotherapy, 2015; 4: [66][67][68][69][70][71][72][73][74][75][76] tal aspects of emotional states and expressing emotional suffering by means of somatic symptoms [3]. The ICD-10 lacks a separate diagnostic category related to psychosomatic illnesses.…”
Section: Introductionmentioning
confidence: 99%